The Star-Formation History of Massive Galaxies - Schael, Anita M (The University of Edinburgh, 2009)
This thesis presents multi-frequency data, galaxy identifications, estimated redshifts, and derived physical properties for the sub-millimetre source sample produced by the SCUBA HAlf Degree Extragalactic Survey (SHADES). SHADES is the largest, complete, sub-millimetre survey undertaken to date, and the aim of this work is to exploit this survey to study the evolution of sub-mm selected galaxies at high redshift, explore their possible connectionwith localmassive ellipticals, and to test current models of galaxy formation. The SHADES sample was selected from 850 micron images made with the submillimetre camera SCUBA at the James Clerk Maxwell Telescope. These submillimetre maps cover a total area of 720 arcmin2 split between two well-studied extra-galactic survey fields, the Lockman Hole East and the Subaru/XMMNewton Deep Field (SXDF). The resulting sample of 120 sub-millimetre sources is the focus of this thesis. Here the wealth of information provided by deep radio, optical, near-infrared and mid-infrared imaging of the two SHADES fields is exploited to complete the identification of the SHADES sample, and then to derive a robust redshift estimate for every sub-millimetre source. Where possible this is achieved from the optical+ infrared photometry using a new two-component redshift estimation code developed specifically to deal with starbursting galaxies with potentially highly stochastic star-formation histories. The effectiveness of this code is demonstrated via comparison with the small subset of SHADES source which possess robust spectroscopic redshifts. For those galaxies which are too faint for effective redshift constraints to be provided by the existing optical+infrared photometry, the information on the long-wavelength spectral energy distribution provided by the radio+submm photometry is utilised to provide cruder constraints or limits on redshift. The result is the first complete and unbiased estimate of the redshift distribution of the bright extragalactic sub-millimetre galaxy population. It is found that the brightest sub-mm sources are confined to the redshift range 2 < z < 4, while more moderate luminosity sources span the full range of redshift out to z ∼ 5. The fits to themulti-frequency photometry provided by the redshift estimation technique are also used to derive estimates of the stellar mass, and star-formation history of each SHADES galaxy. The average derived stellar mass is ∼ 3 × 1011 M⊙ and it is found that the violent starburst powering the sub-millimetre emission typically contributes less than 10% of the stellar mass of the galaxy which has been assembled prior to the “current” starburst event. The distributions of redshift, stellar mass, and star-burst ages are compared with the predictions of a range of galaxy models, including the suite of models originally used to motivate the SHADES survey in van Kampen et al. (2005), and themost recent incarnation of the Durhamsemi-analytic galaxy formationmodels described by Swinbank et al. (2008). It is found that the redshift distribution and sub-mmflux versus redshift for bright sub-mmgalaxies can be reproduced best by one of the van Kampen models, which is based on semi-analytic modelling with a Chabrier IMF. We can rule out the non-semi-analytic prediction models and the Durham semi-analytic model with a top-heavy IMF. However the stellar masses are systematically underpredicted by all of the models. Either the stellar masses derived from the SHADES data have been systematically over-estimated, or the models need to be modified (perhaps by the inclusion of AGN feedback) to allow larger galaxy masses to assembled prior to z ∼ 2. Finally, it is demonstrated that themass in place prior to the observed starburst cannot have been produced by an analogous super-burst at higher redshift, but rather requires to have been assembledmore gradually over a timescale of ∼ 1−2 Gyr. It is thus concluded thatmassive galaxies undergo theirmost violent phase of star formation at redshifts 2 < z < 4, but that the enormous starbursts which lead to detection in current sub-millimetre surveys can only take place in the potential well provided by an already massive galaxy. This supports a scenario in which bright sub-millimetre galaxies are indeed the progenitors of the massive elliptical galaxies found in the local Universe.
Keywords: Astronomy; Galaxy formation; Star formation history